Análise de necessidades de formação: uma prática reveladora de objetivos da formação docente - Almeida, Maria Julia de Paiva (2014)
In recent years, in Brazil, researches in the area of education have been focused on the study of the necessities of formation, by the practice of necessity analysis, to subside the continued teacher formation programs. This research on the necessity of the formation of literacy teachers in the initial years of primary education originated in our discussions in academia, regarding the issues of retention and evasion related to basic literacy teaching in Brazilian public schools. We defined as a goal: to know the necessities of the formation of literacy teachers from Odila Leite Municipal Elementary School, Natal/RN, which focuses on the literacy teaching on that level of education and in Adult and Youth Education. The object is the necessities in these teachers formation. The thesis is that the literacy teacher reveals/constructs formation necessities when speaking of her practice, when exerting said practice or even when producing teaching materials which subside that practice; in other words, when making the theoretical/practical relation related to literacy teaching. The approach is qualitative, according to which the natural environment is the source for data collection; the focus of interest is the process of knowledge construction, and fundamental importance is given to the meanings constructed by the subjects. We comprehended that necessity is a socially constructed subjective phenomenon, and that necessity analysis allows the revelation of formation objectives. We used the case study as a methodological strategy which permits: studying a well-defined entity, [ ] as well as an academic institution; the global comprehension of the phenomenon of interest; discovering what is most essential and characteristic in the object. We counted with 17 teachers, 3 of which had their teaching practices observed. We observed the school routine, analyzed the main class documents and plans and interviewed the 17 teachers. We triangulated the data obtained by the routine observation, the observation of the three teachers practices and by the document analysis, next, we triangulated this data with the data from the analyzing the interviews with the 17 teachers. Such procedures reveal formation necessities in those teachers , such as: studying child cognitive development; reviewing the concepts of literacy teaching; reviewing fundaments of written language psychogenesis; reflecting on reading practices and literature; reflecting on the practice of daily planning; reflecting on the school s material conditions and the family/school relation. We concluded that researches of this nature contribute to the orientation of teacher formation programs